Theoretical study of a novel Sliding-Vane Rotary Pump – structure analysis and its chamber pressure. (4th March 2017) - Tang, J. F.; Wu, X. D.; Wu, Y. Q.; Han, G. Q.
ABSTRACT: A new rotary volumetric pump, called a 'Sliding-Vane Rotary Pump (SVRP)', which was applied in the Xinjiang oilfield for its resistance to high temperature in well downhole was introduced in this paper. Compared to a conventional artificial lift pump, the volumetric efficiency and the energy saving are the obvious advantages of this pump. Based on the analysis of SVRP's internal mechanical structure, the inner pressure distribution model of SVRP was established according to the compressibility of crude oil. Then, the load torque of both sides of the sliding-vane was calculated on the basis of the SVRP chamber pressure distribution model that has been established in the paper, and then the SVRP load torque curve was plotted. The pump load torque curve trend is consistent with the trend of the pressure curve. A conclusion was drawn that the 'sealed angular difference' of SVRP should be optimized to reduce the pump leakage and load torque for the reason of chamber pressure difference. The pressure variations of the pump chamber in the entire rotation period were analyzed in order to provide a theoretical pump leakage and pump efficiency analysis premise. It also can be utilized to explain the unbalanced pressure on pump bearing.